Experimental and numerical investigations on the bidirectional thermal contact performance - Chen Wang; Mingjun Qiu; Huijing Liu; Jun Hong; Feiyu Gu; Lifei Chen; Tao Wang; Hao Guan; Qiyin Lin (Case Studies in Thermal Engineering)
The bidirectional thermal performance of electronic components and thermal rectifiers determines their working performance. However, limited attention has been paid to it while considering the rough surface morphology. This study innovatively employed a combined approach of numerical analysis and experimental testing to investigate the bidirectional thermal contact performance. Initially, the effects of pressure, temperature, and thermal conductivity on the thermal contact resistance (TCR) are investigated. Subsequently, bidirectional thermal contact performance consisting of TCR ratio and thermal rectification coefficient was analyzed under varying temperatures and pressures. Additionally, a prediction model for TCR was developed using the Levenberg-Marquardt (L-M) algorithm. The findings indicate that the maximum error between the experimental and numerical results at pressures from 0.5 to 4.0 MPa is below 13 %. As the pressure increases from 1.0 to 5.0 MPa, the TCR ratio increases from 1.463 to 2.333, while the thermal rectification coefficient increases first and then decreases, varying between 1.038 and 1.085. These results suggest an optimal TCR ratio threshold for maximizing thermal rectification coefficient. Moreover, the prediction model demonstrates a high coefficient of determination (R-squared, 96.45 %). The study provides a theoretical basis for accurate prediction of bidirectional thermal performance and improving thermal rectification effect by regulating TCR.